Roman holidays : American writers and artists in nineteenth-century Italy - Martin, Robert K., 1941-; Person, Leland S. (University of Iowa Press, 2002)
Featuring essays by twelve prominent American literature scholars, Roman Holidays explores the tradition of American travel to Italy and makes a significant contribution to the understanding of nineteenth-century American encounters with Italian culture and, more specifically, with Rome.